2017
DOI: 10.1007/s00572-017-0783-y
|View full text |Cite
|
Sign up to set email alerts
|

Rhizophagus irregularis MUCL 41833 transitorily reduces tomato bacterial wilt incidence caused by Ralstonia solanacearum under in vitro conditions

Abstract: Bacterial wilt caused by Ralstonia solanacearum is one of the world's most important soil-borne plant diseases. In Martinique, French West Indies, a highly virulent new pathogenic variant of this bacterium (phylotype IIB/4NPB) severely impacts tomato production. Here we report on the effect of R. solanacearum CFBP 6783, classified in phytotype IIB/4NPB, on tomato plantlets grown under strict in vitro culture conditions in the presence or absence of the arbuscular mycorrhizal fungus Rhizophagus irregularis MUCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Root rot is caused by a complex of several soil-borne plant pathogens, andpathogens and is are a major problem in plant production leading to serious economic loss for farmers . The arbuscular mycorrhizal (AM) symbiosis is known to improve root health with biocontrol features against a broad range of abiotic (Birhane et al 2018) and biotic agentssoil borne pathogens , including fungi , bacteria (Chave et al 2017) and oomycetes . Confirmedly, research has shown that AM can increase Cucumis sativus root health when infected by Fusarium oxysporum , Rhizoctonia solani (Chandanie et al 2009) and Pythium ultimum .…”
Section: Introductionmentioning
confidence: 99%
“…Root rot is caused by a complex of several soil-borne plant pathogens, andpathogens and is are a major problem in plant production leading to serious economic loss for farmers . The arbuscular mycorrhizal (AM) symbiosis is known to improve root health with biocontrol features against a broad range of abiotic (Birhane et al 2018) and biotic agentssoil borne pathogens , including fungi , bacteria (Chave et al 2017) and oomycetes . Confirmedly, research has shown that AM can increase Cucumis sativus root health when infected by Fusarium oxysporum , Rhizoctonia solani (Chandanie et al 2009) and Pythium ultimum .…”
Section: Introductionmentioning
confidence: 99%
“…It is a way to adapt to the trend of “green agriculture”. Many biocontrol agents have been isolated and tested for their activity against bacterial wilt, including Rhizophagus irregularis [ 18 ], Pseudomonas fluorescens [ 19 ], Bacillus amyloliquefaciens [ 20 ], and Stenotrophomonas maltophilia [ 21 ]. In this study, we isolated and identified three new bacterial species with high activity against R. solanacearum .…”
Section: Introductionmentioning
confidence: 99%
“…FE14 studied the potential of Crotalaria juncea as a sanitizing and mycorrhizal plant in diversified open-field market-gardening systems under tropical conditions (Deberdt et al 2015;Chave et al 2017). The objectives assigned to CPs were to reduce the incidence of two soilborne pests, bacterial wilt and root-knot nematodes, and to increase tomato mycorrhization.…”
Section: Actionable Knowledge Emerged From the Modalities Of Use Of C...mentioning
confidence: 99%